Quantitative Susceptibility Mapping Detects Neovascularization of the Epiphyseal Cartilage After Ischemic Injury in a Piglet Model of Legg-Calvé-Perthes Disease - Johnson, Casey P. (J Magn Reson Imaging, 2018)
BACKGROUND: Legg-Calvé-Perthes disease (LCPD) is a childhood hip disorder thought to be caused by disruption of blood supply to the developing femoral head. There is potential for imaging to help assess revascularization of the femoral head. PURPOSE: To investigate whether quantitative susceptibility mapping (QSM) can detect neovascularization in the epiphyseal cartilage following ischemic injury to the developing femoral head. STUDY TYPE: Prospective. ANIMAL MODEL: Right femoral head ischemia was surgically induced in 6-week-old male piglets. The animals were sacrificed 48 hours (n = 3) or 4 weeks (n = 7) following surgery, and the operated and contralateral control femoral heads were harvested for ex vivo MRI. FIELD STRENGTH/SEQUENCE: Preclinical 9.4T MRI to acquire susceptibility-weighted 3D gradient echo (GRE) images with 0.1 mm isotropic spatial resolution. ASSESSMENT: The 3D GRE images were used to manually segment the cartilage overlying the femoral head and were sub-sequently postprocessed using QSM. Vessel volume, cartilage volume, and vessel density were measured and compared between operated and control femoral heads at each timepoint. Maximum intensity projections of the QSM images were subjectively assessed to identity differences in cartilage canal appearance, location, and density. STATISTICAL TESTS: Paired t-tests with Bonferroni correction were used (P < 0.008 considered significant). RESULTS: Increased vascularity of the epiphyseal cartilage following ischemic injury was clearly identified using QSM. No changes were detected 48 hours after surgery. Vessel volume, cartilage volume, and vessel density were all increased in the operated vs. control femoral heads 4 weeks after surgery (P = 0.001, 0.002, and 0.001, respectively). Qualitatively, the increase in vessel density at 4 weeks was due to the formation of new vessels that were organized in a brush-like orientation in the epiphyseal cartilage, consistent with the histological appearance of neovascularization. DATA CONCLUSION: QSM can detect neovascularization in the epiphyseal cartilage following ischemic injury to the femoral head.